PENGARUH PENDIDIKAN KARAKTER TERHADAP PERILAKU PESERTA DIDIK KELAS III DI SD AL – MUJTAHIDIN KOTA SORONG - Wardah Salwa Aqilah; Nur Fadillah Busran; Sulian Taufiq; Oki Sandra Agnesa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education is one of the strategic efforts in shaping the personality and behavior of students with noble character. This study aims to determine the effect of character education on the behavior of third-grade students at SD Al-Mujtahid Sorong City. The study used a quantitative approach with a correlational survey research design. The research sample consisted of 60 third-grade students selected using the total sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis used simple linear regression test. The results showed that character education has a positive and significant effect on the behavior of third-grade students at SD Al-Mujtahid Sorong City with a coefficient of determination (R²) of 0.621, meaning that character education contributes 62.1% to changes in student behavior. The F-count value of 94.73 with a significance of 0.000 < 0.05 indicates that the regression model used is significant. The implementation of character education through habituation of religious values, honesty, discipline, social care, and responsibility has been proven to significantly improve the quality of student behavior in daily life in the school environment.